Agentes transmitidos por carrapatos (Acari: Ixodidae) em pequenos mamíferos silvestres não voadores na Amazônia Mato-Grossense, Brasil - Colle, Ana Cláudia (2019)
Among invertebrates, ticks are the major vectors of animal pathogens, and second group of ectoparasites, to transmit a greater variety of pathogens to humans. Rodents and marsupials are known to act as ecological links in the transmission chains of tick-borne diseases. Small non- volant mammals (marsupials and small rodents) were captured in three municipalities (Alta Floresta, Sinop and Cláudia) emplaced within the Amazonian biome of the Mato Grosso State in midwestern Brazil. A total of 230 specimens (78 rodents and 152 marsupials) were trapped. The specimens were inspected for the presence of ticks. These were collected and selected for molecular analysis of Rickettsia spp. Animal tissues (liver, spleen and blood) were screened by molecular analyses for the detection of Babesia, Theileria, Coxiella, Hepatozoon, and Anaplasmataceae agents. Hepatozoon and Babesia agents were detected in common opossums (Didelphis marsupialis). In contrast, all collected samples (blood, liver or spleen) of small mammals were negative for the genus Theileria, Cytauxzoon, Coxiella and the family Anaplasmataceae by polymerase chain reaction (PCR) assays. Phylogenetic analyses inferred from partial sequences of 18S rRNA gene highlighted new Hepatozoon spp. and Babesia spp. haplotypes. Amblyomma cajennense s.s., Amblyomma coelebs and Amblyomma scalpturatum were positive for Rickettsia amblyommatis, whereas Amblyomma humerale e Amblyomma sp. was positive for Rickettsia sp. here denominated Sinop hallotipo. We recorded for the first time in this study the tick-host associations between: a) nymphs of A. cajennense s.s. and Caluromys philander; b) nymphs of A. humerale and Marmosa constantiae; c) larvae and nymphs of A. humerale and Metachirus nudicaudatus; d) larvae of A. humerale and Proechimys roberti; e) larvae of A. coelebs and M. nudicaudatus; f) larvae and nymphs of A. scalpturatum in D. marsupialis. Future studies regarding the importance of common opossums (D. marsupialis) in the epidemiological cycles of Hepatozoon and Babesia agents under natural conditions in the Amazonian biome are necessary. In addition to studies that identify possible Rickettsia species in circulation in this biome, its hosts and implications for animal and human health.